Lightning Effects Technique Comparison in Unity 3D - Syauqi Hidayatul Hakim; Wahyu Andhyka Kusuma (Jurnal Informatika, 2019)
Game developer team especially indie game developer mostly has small number of members and sometimes unbalanced team composition. Sometimes it has more artist than programmer, sometimes it is the opposite. At the same time, consumer will choose game that has a beautiful graphics. This demands of good graphic game can cause problem to unbalanced developer team. Therefore it is needed to know techniques that can utilize many artist or many programmer to create good graphic games. In this articles, we introduce some techniques to create special lightning effects of characters skills in Unity3D. Some of them can be created with good artistic skill. It means that this technique make use of your artist. The other technique created procedurally using Line Renderer from Unity 3D. This technique is friendly for artist since it utilze programmer. At the end of this article, all of those technique will be tested in their performance of its lightness and speed.